No Words for Feelings? Not Only for My Own: Diminished Emotional Empathic Ability in Alexithymia - Alkan Härtwig, Elif; Aust, Sabine; Heekeren, Hauke R.; Heuser, Isabella (Frontiers in Behavioral Neuroscience, 2020)
The present study has been designed to disentangle cognitive and emotional dimensions of empathy in a group of mentally healthy and highly alexithymic individuals (ALEX, n = 24) and well-matched controls (n = 26) through questionnaire Interpersonal Reactivity Index (IRI) and Multifaceted Empathy Task (MET) used during the fMRI and after the fMRI. Simultaneously, Skin Conductance Response (SCR) has been acquired as an implicit measure of emotional reaction. Results show an impaired emotional empathic ability in alexithymic individuals, with lower levels of SCR and higher activation in prefrontal brain regions such as the ventrolateral prefrontal cortex (VLPFC) and inferior frontal gyrus (IFG). Cognitive empathy was not impaired in the alexithymic group and the results were accompanied by a higher activation left IFG. The study leads to the conclusion that alexithymia does not only involve a diminished ability to identify and describe one’s own emotions. Furthermore, it is related to a deeper disability of emotion regulation, which becomes visible through impaired emotional concern for others and higher levels of personal distress.